Exelon and Pepco Holdings Inc. Reach Settlement Agreement with Montgomery and Prince George's Counties in Maryland (Business Wire, 2015)
The settlement, which is subject to the approval of the Commissioners of the PSC, was filed by Exelon and Pepco Holdings and signed by Montgomery County, Prince George's County, the National Consumer Law Center, National Housing Trust, Maryland Affordable Housing Coalition, the Housing Association of Nonprofit Developers and a consortium of nine recreational trail advocacy organizations led by the Mid-Atlantic Off-Road Enthusiasts (MORE).